MASALAH-MASALAH YANG DIALAMI SISWA SMPN 4 KAMPAR T.P. 2015/2016 - Masri Elpiwati Siregar; Zulfan Saam; Rosmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The objectives of this study are 1) to get the information about the problem of male and female students, 2) to get the information about the emotional conditions of male and female students, 3) to get the information about learning problem of male and female students, 4) to get the information family problems of male and female students, 5) to get the information about social problems of male and female students, 6) to get the information about the problems experienced by male and female students in general, 7) to obtain categories of the problems that experienced by students in general. The data collection technique used questioners related to some students’ problems such as emotional problems, learning problems, family problems, and social problems that created by the writer based on the guidelines with the alternative yes or no answer. The subject of this research is the students of class VII, VIII, IX that taken from saturated sampling technique. The result shows that: 1) The personal problems faced by male students are 55 percents, while female students are 75 percents, 2) The emotional problems faced by male students are 65% and male students are 82 percents, 3) the learning problems face by male students are 57% and female students are 47 percents, 4) the family problems faced by male students are 46 percents while female students are 32 percents, 6) the general problems faced by students are personal, emotional and learning problem. The female students also have the same problems. In general, the description of the problems that faced by male and female students is in few category.Keywords: personal, emotional, learning, family, social